The Wound Healing Potential of Honey and Propolis from Stingless Bees in Acute Wounds - Wafi, Viky Hibatu; Arius, Yudhy; Tua, Ivan Joalsen Mangara; Paramita, Swandari; Sawitri, Endang (Universitas Malahayati, 2025)
ABSTRACT Honey and propolis from stingless bees have been reported to promote wound healing due to their anti-inflammatory, antioxidant, antibacterial, and moisturizing activities. However, variations in compounds and biological activities of these products can arise due to geographical and bee origin differences. This study aimed to investigate the wound healing potential of stingless bee honey and propolis from East Kalimantan in an acute wound animal model. Honey and propolis from stingless bees have been reported to promote wound healing due to its anti-inflammatory, antioxidant, antibacterial, and moisturizing activities. However, variation of compounds and biological activities of these products can arise due to geographical and bee origin differences. This study aimed to investigate the wound healing potential of stingless bee honey and propolis from East Kalimantan in acute wound animal model. A post-test only control group design was employed in this study. Fifteen Wistar rats were divided into 3 groups, i.e., a control receiving tulle and treatment groups receiving stingless bee honey and propolis, respectively. Wound healing activity was evaluated from wound diameter changes and histological evaluations following hole punch wound. Kruskal Wallis test results showed no significant changes in the proliferation phase of wound healing, as reflected by the diameter changes (p = 0.989), the rate of histopathological re-epithelization (p = 0.730) as well as number of fibroblasts (p = 0.779), collagen (p = 0.779), and neovascularization (p = 0.756) among the groups. Honey and propolis from stingless bees have the potential to treat acute wounds in the proliferation phase where their wound healing properties are equivalent to tulle. Keywords: Acute Wound, Stingless Bee, Honey, Propolis.